The trial of sending short message service multidrug‑resistant tuberculosis patients in Indonesia: the chance to increase knowledge and motivation - Syarifah Syarifah; Devi N. Santi (AOSIS, 2023)
Multidrug‑Resistant Tuberculosis (MDR TB) is a threat for the future control of TB disease. In Indonesia, the success rate of MDR TB patient recovery is still very low, following the still low recovery rate of TB patients. This paper aims to discuss the trial result of message delivery containing knowledge and motivation to the MDR TB sufferers. There are about 34 MDR TB patients participating in this research. During the research, everyone received a message in their handphone or the handphone of their family members every day, contained information on medication and motivation to comply with the medication. At the end of the research, the measurement on knowledge and attitude, on the compliance with medication, and on the compliance with laboratory examinations was conducted. The results were compared with the assessment before this intervention was conducted. Out of 32 patients that managed to complete the intervention, the average means of their knowledge and attitude increased significantly. The average mean of knowledge before the intervention was 9.74 to become 10.94, and the average mean of attitude was from 7.06 to become 18.47 (P0.05). Meanwhile, the medication compliance score and the laboratory examination compliance score also changed significantly (P0.05). SMS delivery routinely even in a short period of time managed to change knowledge and motivation of MDR TB sufferers. To conclude, it is necessary to develop recent technology effort in order to scaling‑up MDR TB patients. Existing social channels in the community must be used intensively to reduce this disease negative impact.